Effect of pre-acetylation of hydroxyl functional groups by choline chloride/acetic anhydride on subsequent lignin pyrolysis. (December 2020) - Li, Tengfei; Yin, Yihui; Wu, Shubin; Ma, Hao; Zhang, Fengshan
Highlights: Choline chloride/acetic anhydride shows high efficiency in acetylation of hydroxyl. The acetylation of hydroxyl enhances the H/Ceff and HHV of pine kraft lignin. The content of H-phenols positively related with the acetylation degree of lignin. The acetylation of hydroxyl is beneficial for the improvement of bio-oil yield. Abstract: In this work, an emerging and efficient strategy for the preparation of lignin samples with different acetylation degree by choline chloride/acetic anhydride (ChCl/Aa) treatment of pine kraft lignin (PKL) is reported, and the effects of efficient pre-acetylation of hydroxyl functional groups on subsequent lignin pyrolysis are also systematically investigated. The results show that the ChCl/Aa displays a high acetylation efficiency towards the aliphatic hydroxyl ( 99.1%) and phenolic hydroxyl ( 94.0%) of PKL, which enhances the hydrogen to carbon effective ratio of PKL. Noticeably, the ChCl/Aa has a slight effect on β-O-4 of PKL, and the acetylation of hydroxyl is beneficial for the improvement of the maximum degradation rate of PKL. In addition, the acetylation of hydroxyl is also significantly contributed to the increment of the pyrolysis bio-oil yield. Importantly, the relative content of the H-phenols obtained from acetylated lignins pyrolysis shows a positive correlation with the acetylation degree of hydroxyl.